Influence of No-till and conventional tillage on the number of earthworms in crops of spring barley of the Right-Bank Forest-Steppe of Ukraine - Танчик, С. П.; Одарченко, О. М. (Scientific Progress & Innovations, 2016)
The effect of No-till and conventional tillage on the number of earthworms in the plow layer of typical black earth in spring barley of Right-Bank Forest-Steppe was researched. It was established that the absence of tillage and crop residues accumulation on soil surface under «direct» sowing had a positive influence on the population of earthworms, which led to increase in their number by 2,6 times compared to plow. In plowing variant the amount of earthworms was reducing from sowing to harvesting of spring barley more than 9 times, while in case of No-till it decreased in 2,2 times.